A MATHEMATICAL STUDY OF THE SRAFFIAN MODEL - Luis J. Hall (Revista de Ciencias Economicas, 2013)
This paper has two primary objects. On the one hand, it presents a rigorous derivation of the Sraffa model recurring to some theorems discovered by Frobenius and Perron at the beginning of the twentieth century. This presentation is used to study the concept of productive economies or surplus economies, the solution to the price system and also to provide a clear derivation of the concept of the Standard Commodity.